International review of cytology : a survey of cell biology. - Jeon, Kwang W. (International review of cytology, 2002)
International Review of Cytology presents current advances and comprehensive reviews in cell biology- both plant and animal. Articles address structure and control of gene expression, nucleocytoplasmic interactions, control of cell development and differentiation, and cell transformation and growth. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. Key Features * Authored by some of the foremost scientists in the field * Provides up-to-date information and directions for future research * Valuable reference material for advanced undergraduates, graduate students and professional scientists.